An introduction to computer aided production management - Childe, Stephen J. (Chapman & Hall, 1997)
The control of manufacturing operations is of crucial importance in industry. The correct regulation of manufacturing activities makes the difference between meeting and missing customer requirements. Nowadays computerised solutions are available as an aid to production management. However, many companies proceed to use sophisticated computer tools without first understanding the basic operating principles. This book is written for students of manufacturing systems as well as people in industry who need a concise explanation of the concepts of Computer Aided Production Management (CAPM) or who may be looking for new ideas.